A comparison of the planning systems in Ireland and Northern Ireland : A joint paper by the Oireachtas Library & Research Service and the Northern Ireland Assembly Research and Information Service.: A joint paper by the Oireachtas Library & Research Service and the Northern Ireland Assembly Research and Information Service. (2018) - Cave, Suzie; (Librarian), Semple, Maggie; Northern Ireland., Assembly., Research and Information Service,; Ireland., Oireachtas Library & Research Service,
No abstract available